Re-Reading Raphael Samuel: Politics, Personality and Performance. Issue 1 (2nd January 2017) - Scott-Brown, Sophie
ABSTRACT: For British historian Raphael Samuel, history and politics were inextricable. Best known as the founder of the history workshop movement, the controversial historian took his stance on the democratisation of history-making, becoming an outspoken advocate for public history. Despite making a significant contribution to contemporary historiography, he remains a neglected, even disparaged, figure. This paper contends that the most significant aspect of Samuel's historical work was not one or other theory of history or argument about the past but his entire way of being an historian. Samuel embodied as much as expressed his ideas, consciously using his personality as a powerful political tool. It is further argued that conventional approaches to intellectual history, focusing on textual outputs, do not fully recognise the significance of performative modes of thinking. Theoretical approaches to performance as identity offer important insight here but can be too schematic in their view of applied and enacted thought. A biographical approach, by contrast, provides the intimate perspective necessary to fully appreciate the fluidity and complexity of such a personality. The paper first situates Samuel in the context of his earlier life, focusing on how and why he created such a public persona and how he adapted it in response to changing circumstances. It then considers the implications and effectiveness of this persona by assessing how it was perceived and narrated by others, acknowledging, in the process, why different groups engaged with and interpreted it differently.